#TITLE_ALTERNATIVE# - PUTRA (NIM 15102044), FAJAR
Image matching can be defined as identification and measurement of similarity features in two or more overlapping photographs. There are many images matching technique has been known, one of them which is used very often is area based matching (ABM). This technique is based on correlation value to determine the level of success of a matching. Some ABM techniques are single vector correlation (SVC), separate channel mean value (SCMV), weighted channel mean value (WCMV), and different correlation (DC). Photograph image which used for mapping in photogrammetry usually impure with noises and will reduce its quality, so data qualities of a photograph determine level of success of a matching process. Noise sensitivity of ABM technique will be used to choose the best technique. Therefore in this research will be used level of sensitivity to noise and correlation value in ABM techniques to choose the best technique.